An updated floristic list for the Pedregal de San Ángel reserve, Mexico D.F. - Valiente-Banuet, Alfonso; de Luna García, Efraín (Instituto de Ecología, A.C., 1990)
The Pedregal of San Angel reserve, located in the campus of the Universidad Nacional Autónoma de México, characterized by a xerophilous scrubland vegetation, has been considered as a place of high floristic richness since the lastcentury. Considering that the original area occupied by the scrubland has been reduced from 4000 to 1 24.5 ha, it is important to analyze the number and ¡dentity of the species that currently can be found in the area. In this work we report that the reserve has 301 species of angiosperms grouped in 61 families.Considering available floristic information of this cpmmunity, we estímate that the original number of species was approximately 350. Of this number it is still possible to find 226 species. This figure is higher than expected according to the empirical relation ofthetheoryof island biogeography. The sources of newly recorded species are discussed in the context of diaspore dispersión from adjacent oak forests and the introduction of propagules in the soil transported into the University gardens from other sites in the Distrito Federal. Local extinction of taxa is associated to urbanization and robbery of ornamental species, activities that have not ceased.